Effectiveness of XP-Endo Finisher and Passive Ultrasonic Irrigation in the Removal of the Smear Layer Using two Different Chelating Agents - AntonioJesus Conde Villar; Gaizka Loroño; Roberto Estevez; Gianluca Plotino; Rafael Cisneros (Shiraz University of Medical Sciences, 2021)
Statement of the Problem: The smear layer may harbor microorganisms and necrotic pulp tissue, jeopardizing irrigant penetration. Recently, Dual Rinse®, a weak chelating agent, has been introduced to the market. However, its chelating capacity in the final irrigation protocol with different activation systems has not yet been deeply analyzed. Purpose: The aim of this ex vivo study was to evaluate the effectiveness of passive ultrasonic irrigation (PUI) and XP-endo Finisher (XP) on smear layer removal in combination with two chelating agents, ethylenediaminetetraacetic acid (EDTA) and etidronic acid (HEDP). Materials and Method: This in vitro, experimental study evaluated fifty-two single-rooted human teeth were standardized to 16 mm in length. Root canal instrumentation was performed by the ProTaper Gold system up to the F4 file. The apical end of the samples was sealed with wax to simulate a closed system. Teeth from group 1 (n=24) were irrigated with 3% sodium hypochlorite (NaOCl) and 17% EDTA, while teeth from group 2 (n=24) were irrigated with 3% NaOCl mixed 9% HEDP. Both groups were divided into two subgroups (n=12) depending on the activation system used: XP (group XP-EDTA and XP-HEDP) or PUI (group PUI-EDTA and PUI-HEDP). The specimens were evaluated by scanning electron microscopy at 3, 5 and 8mm from the apex. Statistical analysis was performed using ANOVA and Bonferroni tests considering p> 0.05 as significant. Results: PUI-EDTA was the most effective at removing the smear layer, with a statistically significant difference from XP-EDTA (p< 0.042) and group XP-HEDP (p< 0.003). There were no statistically significant differences among the other groups. Conclusion: Under the conditions of this ex vivo study, no activation system was able to completely remove the smear layer from the root canal walls. However, the combination of NaOCl with ultrasonically activated EDTA obtained better results than the other treatments.